EVALUATING THE INTERNET - Lehmann, Susan; Schultz, Norah (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
The purpose of this exercise is to gain experience locating information on the internet and gauging its reliability. This exercise is crucial before beginning any of the other exercises in the book. You will be directed to find your university’s site, or another site created by a university library system, that presents some guidelines for judging the quality of different information sources. The exercise will then guide you through the process of evaluating the various types of sites put on the internet by governments, universities, and other organizations.